An investigation on the influence of aluminium oxide nano-additive and honge oil methyl ester on engine performance, combustion and emission characteristics. (February 2020) - Soudagar, Manzoore Elahi M.; Nik-Ghazali, Nik-Nazri; Kalam, M.A.; Badruddin, Irfan Anjum; Banapurmath, N.R.; Bin Ali, Mohamad Azlin; Kamangar, Sarfaraz; Cho, Haeng Muk; Akram, Naveed
Abstract: The potential use of aluminium oxide nanoparticles as nanofuel additives was investigated on honge oil methyl ester and diesel fuel blend. The nanofuel blends were prepared by dispersing aluminium oxide in varying quantities in a HOME(B20) (20% biodiesel+80% diesel). Sodium dodecyl sulfate (SDS), an anionic surfactant, was used for a stable dispersion of aluminium oxide nanoparticles in the fuel blends. HOME(B20) fuel with concentration levels of 20, 40, and 60 ppm of aluminium oxide nanoparticles (HOME20, HOME2040 and HOME2060) with varying ratios of SDS surfactants were prepared using ultrasonication technique. The investigated properties of diesel, honge oil biodiesel and nanofuel blends were in agreement with the ASTM D6751-15 standards. The dispersion and homogeneity were established and characterized by using the Ultraviolet–Visible (UV–Vis) spectrometry. The UV–Vis spectrometry results illustrated an increase in absorbance level with a relative increase in the concentration of surfactant. The highest absolute value of UV-absorbency was observed for a mass fraction of 1:4 (Al2 O3 NPs to SDS ratio). The investigation was performed at a constant speed of 1500 rpm, and BP of 0 kW, 1.04 kW, 3.12 kW, 4.16 kW and 5.20 kW. The fuel HOME2040 demonstrated an overall improvement in the engine parameters, the brake thermal efficiency (BTE) enhanced by 10.57%, while there was a decline in brake specific fuel consumption (BSFC) by 11.65% and the engine exhaust emission: HC, CO, and smoke reduced by 26.72%, 48.43%, and 22.84%, while the NOx increased by 11.27%. Similarly, the addition of aluminium oxide nanoparticles in HOME(B20) fuel blend resulted in decent reduction in the combustion duration (CD), ignition delay period (ID), improvement in the peak pressure, and a marginal increase in heat release rate (HRR) and cylinder pressure at maximum loading conditions. Based on the experimental results, it is concluded that the aluminium oxide nanoparticles in HOME(B20) fuel demonstrated an overall improvement in the engine characteristics. Highlights: Al2 O3 NPs-SDS surfactant ratio of 1:4, demonstrated highest UV–Vis absorbance. Honge yielded 85% HOME, nanofuel properties were comparable with ASTM standards. HOME2040 nanofuel enhanced BTE by 10.57% and reduced BSFC by 11.65%. HOME2040 reduced emissions of CO, HC and smoke by 47.43%, 37.72% and 27.84%. The HRR, PP improved and CD, ID reduced, while NOX increased for nanofuel blends.